2022
DOI: 10.1007/s00296-022-05106-3
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent myopathy and inflammatory cardiac disease in COVID-19 patients: a case series and literature review

Abstract: Adult COVID-19 patients can present with acute muscle and/or cardiac involvement. Our study aims to describe the incidence and characteristics of patients with the co-occurrence of COVID-19 myopathy and inflammatory cardiac disease. We retrospectively reviewed all COVID-19 patients admitted to a large tertiary center to assess the co-occurrence of myopathy and inflammatory cardiac disease. We conducted a literature review of prior relevant case reports. There were three COVID-19 patients with concurrent involv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
12
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 36 publications
1
12
1
Order By: Relevance
“…Extra‐pulmonary manifestations and concurrent diseases were prevalent in our study population and consistent with prior studies 19,20 . Extra‐pulmonary manifestations may either appear in more than one organ simultaneously or may be the sole initial presentation of COVID‐19 21,22 . Additional complications secondary to any infectious etiology, such as dehydration or diabetic ketoacidosis, also occur among COVID‐19 patients.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Extra‐pulmonary manifestations and concurrent diseases were prevalent in our study population and consistent with prior studies 19,20 . Extra‐pulmonary manifestations may either appear in more than one organ simultaneously or may be the sole initial presentation of COVID‐19 21,22 . Additional complications secondary to any infectious etiology, such as dehydration or diabetic ketoacidosis, also occur among COVID‐19 patients.…”
Section: Discussionsupporting
confidence: 87%
“…19,20 Extra-pulmonary manifestations may either appear in more than one organ simultaneously or may be the sole initial presentation of COVID-19. 21,22 Additional complications secondary to any infectious etiology, such as dehydration or diabetic ketoacidosis, also occur among COVID-19 patients. While these complications may be precipitated in part by the underlying infection, a delay in their treatment can still put the patient at risk.…”
Section: Discussionmentioning
confidence: 99%
“…However, it remains unclear whether patients with IIMs after COVID-19 differ from those with traditional IIMs. While muscle damage, such as myalgia, myasthenia gravis, and elevated CK levels, is common in individuals with SARS-CoV-2 infection [13], our study found that cardiac damage is more prominent among patients with a history of SARS-CoV-2 infection who also have IIMs. This conclusion was supported by increases in cTnT and HBDH levels as well as scores re ecting cardiac disease activity.…”
Section: Discussioncontrasting
confidence: 46%
“…SARS-CoV-2 can also cause a wide variety of extrapulmonary symptoms owing to its inflammatory effects. For example, cardiac (myocarditis, pericardial effusion, shock), renal (glomerulonephritis), hematological (thrombocytopenic purpura, anemia), neurological (Guillain–Barré syndrome, meningoencephalitis, optic neuritis), and musculoskeletal (myositis, arthritis) complications have been reported[ 10 , 27 - 31 ].…”
Section: Discussionmentioning
confidence: 99%